On the transformation of the linear differential equation into a system of the first order equations - Ayzatsky, M.I. (Вопросы атомной науки и техники, 2019)
The generalization of the transformation of the linear differential equation into a system of the first order equations is presented. The proposed transformation gives possibility to get new forms of the N-dimensional system of first order equations that can be useful for analysis of the solutions of the N-th-order differential equations. In particular, for the third-order linear equation the nonlinear second-order equation that plays the same role as the Riccati equation for second-order linear equation is obtained. Представлено узагальнення перетворення лінійного диференціального рівняння в систему різницевих рівнянь першого порядку. Запропонована трансформація дає можливість отримати нові форми N-вимірної системи рівнянь першого порядку, які можуть бути корисними для аналізу розв'язків диференціальних рівнянь. Зокрема, для лінійного диференціального рівняння третього порядку отримано нелінійне рівняння другого порядку, яке відіграє ту ж саму роль, що і рівняння Ріккаті для лінійного рівняння другого порядку. Представлено обобщение преобразования линейного дифференциального уравнения в систему разностных уравнений первого порядка. Предложенное преобразование дает возможность получить новые формы N-мерной системы уравнений первого порядка, которые могут быть полезны для анализа решений дифференциальных уравнений третьего порядка. В частности, для линейного дифференциального уравнения третьего порядка получено нелинейное дифференциальное уравнение второго порядка, которое играет ту же роль, что и уравнение Риккати для линейного дифференциального уравнения второго порядка.